Fermented Foods: Kefir - Julia R. Skinner (EDIS)
Kefir is a fermented dairy beverage made from milk and kefir grains containing yeast and bacteria. This publication describes how kefir is made and its potential health effects for consumers. Written by Julia R. Skinner, and published by the UF/IFAS Food Science and Human Nutrition Department, July 2024.